Menopausal Symptom Burden, Quality of Life, Healthcare-Seeking Behavior, and Treatment Satisfaction: A Cross-Sectional Study of Romanian Women - Andrei Pescaru; Flavia Crișan; Radu Ioan Lala; Adrian Cosmin Ilie; Norbert Wellmann; Adelina Marițescu; Alaviana Monique Faur; Daian Ionel Popa; Roxana Folescu (Healthcare, 2026)
Background/Objectives: Menopausal symptoms can impair quality of life and influence healthcare use. This study examined symptom burden, menopause-specific quality of life, healthcare seeking, consultation delay, treatment satisfaction, and associated demographic and clinical factors among Romanian women. Methods: This cross-sectional study included 204 peri- and postmenopausal women. We assessed symptoms and quality of life using the Menopause Rating Scale (MRS) and the Menopause-Specific Quality of Life Questionnaire (MENQOL). We compared groups, ran Spearman correlations, and used multivariable linear regression to identify demographic and clinical factors associated with MENQOL. We excluded MRS from the regression because of construct overlap, and restricted delay analyses to care seekers. Results: Care seekers had higher MRS (18.0 vs. 14.5; p = 0.041) and MENQOL scores (3.95 vs. 3.26; p = 0.009). MRS and MENQOL were strongly correlated (ρ = 0.858; p < 0.001), but consultation delay was not associated with either outcome among care seekers. In the adjusted model, higher BMI, postmenopausal stage, greater comorbidity burden, and menopause-medication use were associated with poorer quality of life (adjusted R2 = 0.138). Treatment-satisfaction correlations were inverse but exploratory. Conclusions: Menopause-specific quality of life varied according to body composition, reproductive stage, general health burden, and treatment context. Clinical assessment should integrate these factors and review persistent symptoms among treated women. The cross-sectional findings do not establish causality or treatment effectiveness.